Knowledge and Attitude Influence on Oral Hygiene Practices among University Dental Students with Fixed Orthodontic Appliances - Davin; Maorina; Stevanus Daniel (Open Access Indonesian Journal of Medical Reviews, 2025)
Fixed orthodontic appliances can complicate oral hygiene maintenance, increasing the risk of dental caries and periodontal diseases. This study aimed to assess the relationship between knowledge, attitude, and oral hygiene practices among university dental students undergoing fixed orthodontic treatment. A cross-sectional study was conducted among dental students at Universitas Prima Indonesia. Data were collected using a self-administered questionnaire that included questions on oral hygiene knowledge, attitude towards oral health, and oral hygiene practices. Descriptive statistics, Chi-square tests, and logistic regression were used to analyze the data. A total of 40 dental students participated in the study. The majority of the participants (95%) had good knowledge about oral hygiene. A positive correlation was found between knowledge and attitude (p=0.027), indicating that students with better knowledge exhibited more positive attitudes towards oral health. Furthermore, students with good knowledge were more likely to perform proper oral hygiene practices, including brushing twice daily (95%), using interdental brushes (97.5%), and visiting the dentist regularly (52.5%). In conclusion, this study highlights the importance of oral health knowledge and positive attitudes in promoting proper oral hygiene practices among dental students with fixed orthodontic appliances. Educational interventions aimed at improving knowledge and shaping attitudes may be beneficial in enhancing oral hygiene behavior and ensuring successful orthodontic treatment outcomes.